Recurrent Chylous Pericardial Effusion and Left Neck Mass - Gilmore, Denis; Colson, Yolonda L. (The Thoracic and Cardiovascular Surgeon, 2012)
We present a case of a woman initially presenting with a neck mass and subsequently found to have generalized lymphatic anomaly with diffuse lymphatic dilation and proliferation involving the mediastinum and pericardium. Intrathoracic involvement of generalized lymphatic anomalies can lead to recurrent pleural effusions, pericardial effusions, and severe respiratory infections. These anomalies cannot be cured and significantly impact quality of life. Multidisciplinary involvement is crucial to maximize symptom relief as surgery to remove lymphatics can be morbid and the disease is usually recurrent.
Keywords: generalized lymphatic anomaly; chylous effusion